Differentiation of Mortality in Men and Women at the Age of 20-64 in Respect of Education and Marital Status - Brajczewski, Czesław; Rogucka, Elżbieta (Anthropological Review, 1992)
The data were compiled during the December 1988. Census of Population. It revealed the existence of a clear cut social gradient in mortality. The further down the scale of educational status - the higher the rate of mortality at all ages between 20-64 years. Marital status of the deceased also influenced the level of mortality.